Motivations and challenges of women entrepreneurship : a study in context of Bangladesh - Zohora, Fatema (2022)
Purpose: The thesis aims to identify the basic motivational factors of women entrepreneurs in Bangladesh to start their own business and ascertain the key challenge factors that obstruct a woman from being an entrepreneur. This study can be helpful for future researchers and policymakers to motivate women to be entrepreneurs. Approach: This study utilizes the qualitative research approach. A multiple case study has been employed as the research design. To find the answers to the research question, semi-structured interviews have been supervised with ten Bangladeshi women entrepreneurs from different business sectors. This thesis administered a within-case analysis to clarify the findings from the interviews and the case studies. Research questions: What are the motivational factors that drive women to be entrepreneurs in developing countries? Why women do not want to be entrepreneurs in developing countries? Is the barrier related to society? Is the family discouraging? Or, do women have lack of motivation? Findings: the entrepreneurs indicated different motivational factors including job-related, self-fulfillment, and personal factors. On the other hand, they mentioned the very basic challenge factors that originated from their families and social attitude. Alt-hough there are also business-related barriers, however mostly they pointed to family opposition as the key barrier. Thus, it is evident that women entrepreneurs are self-motivated as they are willing to create self-employment and continue business operations after enduring these barriers.